2022
DOI: 10.18332/ejm/150582
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among midwives and attitudes toward midwifery: A cross-sectional study from Baden-Württemberg, Germany

Abstract: INTRODUCTION Midwifery services are a cornerstone of maternal care, but the mental health of midwives is at risk in many work settings. The aim of this study was to assess burnout and attitudes toward midwifery among midwives in Baden-Württemberg, Germany. METHODS A cross-sectional online survey among midwives was conducted from 16 October to 10 December 2017. Burnout was assessed using the Copenhagen Burnout Inventory (CBI). RESULTS A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
1
5
0
5
Order By: Relevance
“…Other studies have indicated that the impact of neonatal death is burnout, which is severe enough for midwives to consider leaving the profession [ 14 , 40 ]. The results of this research project suggest that midwives cope more effectively with burnout when they seek social, spiritual, familial or collegial support [ 36 ], a claim that resonated with many midwives in this study, as they sought solace by relying on prayer, family and peers [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have indicated that the impact of neonatal death is burnout, which is severe enough for midwives to consider leaving the profession [ 14 , 40 ]. The results of this research project suggest that midwives cope more effectively with burnout when they seek social, spiritual, familial or collegial support [ 36 ], a claim that resonated with many midwives in this study, as they sought solace by relying on prayer, family and peers [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors can be considered when a midwife experiences the death of a newborn, including the need to counsel the grieving mother, the midwife’s own grief, compassion fatigue, posttraumatic stress, and other influences on the midwives’ psychological well-being, burnout, along with the subsequent impact of this phenomenon on the midwife’s psychological well-being [ 13 , 14 ]. Midwives in sub-Saharan Africa rarely have the time to grieve due to the almost continuous overwhelming patient workloads [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that midwifery work is emotionally straining and is characterized by high levels of occupational stress due to high workload, limited job resources, and workplace support [ 7 , 12 ]. As a consequence, there is a growing body of evidence that suggests a high degree of burnout among midwives in various countries [ [13] , [14] , [15] ]. Burnout among midwives is considered to have a significant adverse impact on individual and public health as it can negatively affect their ability to provide high-quality, compassionate care, potentially leading to medical errors, misjudgments, high turnover at work, and a decrease in patient satisfaction [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gesundheitliche Belastungen könnten sowohl Folge als auch Ursache eines Hebammenmangels sein. In Umfragen vor der COVID-19-Pandemie berichteten freiberufliche sowie angestellte Hebammen in Deutschland regelmäßig über eine hohe Arbeitsbelastung und damit verbundene Überlegungen, aus dem Beruf auszusteigen 3 7 9 17 . In Studien aus anderen Ländern, beispielsweise Australien, Kanada, Norwegen, Schweden oder dem Vereinigten Königreich, wiesen Hebammen häufig Burnout-Symptome auf 18 19 20 .…”
Section: Introductionunclassified
“…Die stärkste mittlere Zufriedenheit bestand mit dem Beruf als Hebamme(1,23 [SD 1,17]), der täglichen Arbeit als Hebamme (0,93 [SD 1,03]) und der Zusammenarbeit mit nicht-ärztlichen Kolleginnen und Kollegen (0,92 [SD 1,12]). Die stärkste mittlere Unzufriedenheit bestand mit der Bezahlung als Hebamme (−1,26[SD 1,21]).…”
unclassified